The nine lives of Christmas - Roberts, Sheila, 1951- (St. Martin's Press, 2011)
After firefighter Zach Stone saves Ambrose from a vicious dog, the cat tries to repay him by moving (uninvited) into his house and fixing his lonely bachelor life. While Zach is buying cat food, he meets Merilee White, a winsome pet store clerk with a fondness for stray cats and big strong men who take them in. Her competition is Zach's no-strings-attached lover, Blair, a haughty cat-hater who insists Zach evict the cat before Christmas.